Health issues among transgenders in urban Pondicherry - Palve, Sachin Bhaskar; N, Seetharaman; T, Lochan; Patil, Rajkumar; A, Lokeshmaran (Indian Journal of Community Health, 2018)
Background: Transgender is an umbrella term for people whose gender identity and expression does not conform to the norms and expectations traditionally associated with the sex assigned to them at birth. Aim & Objectives: To study the health problems among the transgenders, to study the health seeking behaviour of the transgenders, to study the social stigma and discrimination faced by the transgenders and to study the sexual behaviour among the transgenders. Settings and Design: It is a community based, descriptive, cross-sectional, study design done among 121 transgenders (TGs) registered under a Non-Government Organization. Methods and Material: A convenience sampling was undertaken. A pre-designed, pre-tested and self-administered, semi-structured questionnaire in local language was used. Statistical analysis used: Proportion, mean, standard deviation, Kruskal-Wallis & Mann-Whitney test were applied using EpiData and chi-square test was applied using MS Excel. Results: The common places of discrimination faced by the Transgender were public bathrooms for 36 (29.8%), school for 36 (29.8%) TGs and in bus for 29 (24.0%) TGs. 57 (47.1%) had sexual relationship with more than one partner. Tobacco chewing was the commonest form of substance abuse found among the distressed transgenders. (p=0.007). Conclusions: Lower per capita income, no fixed job status; low education status, prevalent health problem of knee joint arthritis, were the main findings among the transgenders. Substance abuse of alcohol and consumption of tobacco products were high and an association was found between products of tobacco consumption to their psychological distress.